2020
DOI: 10.1063/5.0019195
|View full text |Cite
|
Sign up to set email alerts
|

Nano-second exciton-polariton lasing in organic microcavities

Abstract: Organic semiconductors are a promising platform for ambient polaritonics. Several applications, such as polariton routers, and many-body condensed matter phenomena are currently hindered due to the ultra-short polariton lifetimes in organics. Here, we employ a single-shot dispersion imaging technique, using 4 nanosecond long non-resonant excitation pulses, to study polariton lasing in a λ /2 planar organic microcavity filled with BODIPY-Br dye molecules. At a power threshold density of 1.5MW /cm 2 , we observe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…In recent years, polariton BECs have been observed in microcavities containing many different species of organic molecules. [8][9][10][11][12][13][14][15][16][17][18]25,26] In organic microcavities, the Rabi splitting energy, which is the minimum splitting between upper polariton (UP) and LP bands and characterizes the light-matter interaction strength, is usually the order of 0.1-1 eV. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] This large Rabi splitting allows for the realization of polariton condensates at room temperature.…”
Section: Doi: 101002/adom202102034mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, polariton BECs have been observed in microcavities containing many different species of organic molecules. [8][9][10][11][12][13][14][15][16][17][18]25,26] In organic microcavities, the Rabi splitting energy, which is the minimum splitting between upper polariton (UP) and LP bands and characterizes the light-matter interaction strength, is usually the order of 0.1-1 eV. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] This large Rabi splitting allows for the realization of polariton condensates at room temperature.…”
Section: Doi: 101002/adom202102034mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18]25,26] In organic microcavities, the Rabi splitting energy, which is the minimum splitting between upper polariton (UP) and LP bands and characterizes the light-matter interaction strength, is usually the order of 0.1-1 eV. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] This large Rabi splitting allows for the realization of polariton condensates at room temperature. However, the thresholds for condensation under optical excitation in dielectric and plasmonic microcavities containing organic molecules range from P th ≈ 11 to 500 µJ cm −2 , [8][9][10][11][12][13][14][15][16][17][18]25,26] which are still too high for many optoelectronic applications.…”
Section: Doi: 101002/adom202102034mentioning
confidence: 99%
See 1 more Smart Citation
“…1 to fabricate a series of strongly-coupled microcavities containing the molecular dye bromine-substituted boron-dipyrromethene (BODIPY-Br). This dye combines high oscillator strength and relatively high photoluminescence quantum yield, and has previously been shown to undergo polariton-condensation 18 , 34 . Additionally, its photoluminescence (PL) emission lies in a spectral region not easily accessible with traditional inorganic semiconductors (green/yellow), making it desirable for laser applications.…”
Section: Resultsmentioning
confidence: 99%
“…[ 163 ] They found that at a low temperature (<45 K), inefficient phonon–polariton interactions led to change in polariton population and eventually increase in the polariton lasing threshold. Putintsev et al [ 164 ] demonstrate quasi‐steady‐state polariton lasing (nanosecond scale) in a BODIPY‐Br dye λ /2 planar microcavity. Under 4 ns‐long nonresonant excitation, 1.2 ns polariton lasing was achieved, being four orders of magnitude longer than the inherent polariton lifetime.…”
Section: Typical Resonator Architecturesmentioning
confidence: 99%